Experimental approach in apple tree nutrition - Kállay, T.; Szűcs, E. (International Journal of Horticultural Science, 2003)
Authors present synthesis of experimental work, performed in the last decades, for better understanding nutritional behaviour of apple trees and related problems in fruit quality. There were evidences supporting possible deteriorating role of potassium in feeble physiological status of apples, if applied in excess. More intensive studies proved that higher potassium uptake into leaves and fruits might be also the result of increased sink power of individual fruits. Nevertheless early senescence of apples during storage and also sensibility to bitter pit were successfully related to the increased sink power of fruits, casual relations in excessive NPK fertilization, although increase in sink power need further investigations. Impaired weather conditions during early development of fruits, hostile orchard practices in pruning, thinning, irrigation and also unskilled application of growth regulators may also contribute in the enhancement of sink power and in weakened physiological status of apple fruits.